METHYLCOBALAMIN EFFECT ON MECHANICAL BEHAVIOR ALLODYNIA IN RATS SPRAGUE DAWLEY - ENDANG MUTIAWATI (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2014)
Neuropathic pain is an expression of the nerve damage that impaired its excitability, such as increased excitability in the nerve lesion and surrounding healthy nerves as well. It is estimated that the incidence of neuropathic pain ranges between 2-40% of all adult men. Some neuropathic pain can not be cured, such as in patients with diabetes mellitus, trigeminal neuralgia, cervical syndrome, carpal tunnel syndrome, lumbar stenosis, herniated nucleus pulposus and the carcinoma. The pathophysiology of neuropathic pain are complex and not fully understood. Methylcobalamin is a metabolite of vitamin B12 acts as a coenzyme in the formation of methionine from homocysteine. This reaction is useful in the formation of DNA, as well as maintenance of nerve function. Through the methylation reaction, methylcobalamin also plays a role in the formation of lecithin, a protein that plays an important role in the regeneration of peripheral nerves, including the formation of myelin. This study aimed to determine animal mechanical alodinia with or without the administration of methylcobalamin. Twenty male Sprague Dawley rats, aged 2 months, with an average weight of 150-250 g, obtained from the Laboratory LPPT Gadjah Mada University, Yogyakarta. The mice were randomly divided into 4 groups, each consisting of 5 mice. All the rats, their fifth lumbar nerve were ligated. Group I was the control mice (C) 0.9% NaCl given, group II (M1) were given a dose of 50 microg methylcobalamin, group III (M2) were given a dose of 100 microg methylcobalamin, while group IV (M3) were given a dose of 150 microg methylcobalamin 13 weeks provision. For 13 weeks, neuropathic pain behavior was assessed. Neuropathic pain behavior in experimental animals observed about onset, duration and filaments Von Frey numbers that cause mechanical alodinia. Result of the study showed methylcobalamin influence the mechanical alodinia. Based on the results obtained, it is concluded that there was a reduction in neuropathic pain in the methylcobalamin group compared with the control group.